Artificial Intelligent Applications in Smart Cities - Caglayan, Ruhi Zafer; Kayisli, Korhan; Coteli, Resul; Omirgaliyev, Ruslan; Zhakiyev, Nurkhat (Institute of Electrical and Electronics Engineers Inc., 2024)
History shows us that people move towards a more stable lifestyle after undergoing significant changes. During these times, the way communities and buildings were designed started to change too. Different periods in history are known for their standout moments, each bringing its own set of needs and tech breakthroughs. Nowadays, tech keeps evolving. People nowadays aim for a more straightforward life, and technology has been shaping up to meet this need. We live in times highlighted by the rise of smart technology, like artificial intelligence and the Internet of Things, which not only make daily tasks easier but also transform how we think about our cities and personal spaces. This piece focuses on exploring the smart city idea, touching upon various associated subjects. As we delve into these areas, we'll also look at some important research related to them. © 2024 IEEE.
4th IEEE International Conference on Smart Information Systems and Technologies, SIST 2024 -- 15 May 2024 through 17 May 2024 -- Astana -- 201893
Keywords: Artificial intelligence; intelligence systems; Internet of Things; Smart City